2006
DOI: 10.1029/2005gl024713
|View full text |Cite
|
Sign up to set email alerts
|

Tower mast of precipitation over the central Tibetan Plateau summer

Abstract: [1] Over the Tibetan Plateau, solar heating often produces strong convective instability in the atmosphere. Using 3 years (1998 -2000) of Tropical Rainfall Measuring Mission (TRMM) precipitation radar data, our investigations revealed a tower mast shape of precipitation over the Plateau in both height-longitude and height-latitude cross-sections. High rain rate center over the Plateau is located above 6km as a tower penetrating into the midtroposphere against the nearby background, implying a unique latent he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 15 publications
5
69
0
3
Order By: Relevance
“…The former usually has three (or four) layers from rain top to near surface: crystal, mixed ice and water, and droplet collision (evaporation) layer. In contrast, the latter commonly has three layers: crystal, mixed ice and water, and water layer (Liu and Fu 2001;Fu et al 2003Fu et al , 2006. TRMM 2A25 products can offer both the precipitation types and three dimensional rainfall structures (Iguchi et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The former usually has three (or four) layers from rain top to near surface: crystal, mixed ice and water, and droplet collision (evaporation) layer. In contrast, the latter commonly has three layers: crystal, mixed ice and water, and water layer (Liu and Fu 2001;Fu et al 2003Fu et al , 2006. TRMM 2A25 products can offer both the precipitation types and three dimensional rainfall structures (Iguchi et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The vertical cross-sections along the A-B, C-D, and E-F paths in Figure 3a are shown in Figure 4. This shows that the top altitude of the strong convective precipitation system reached above 15 km (Figure 4a), which is slightly lower than the maximum that Fu et al [27] found, in their study of the convective precipitation on the Tibetan Plateau during summer: more than 17 km. The convection of the heavy rain was very strong; its maximum precipitation intensity surpassed 50 mm¡h −1 , and the convective center was at a height of about 5 km above the ground surface.…”
Section: Characteristics Of Vertical Structurementioning
confidence: 69%
“…The convection of the heavy rain was very strong; its maximum precipitation intensity surpassed 50 mm¡h −1 , and the convective center was at a height of about 5 km above the ground surface. The strong convective precipitation clouds showed a columnar shape, whereas Fu et al [27] found a "steamed-bun" shape in their study of the convective precipitation on the Tibetan Plateau during summer-a slight difference. The strongest clouds moving upward from the surface extended to about 12 km (Figure 4b), although the A-B ( Figure 4a) and E-F (Figure 4c) paths extended only to about 10 km.…”
Section: Characteristics Of Vertical Structurementioning
confidence: 94%
See 1 more Smart Citation
“…The PR has a unique capability of detecting 3-dimensional structures of precipitation and also can distinguish stratiform precipitation and convective precipitation on the pixel scale [3][4][5]. These functions make TRMM PR the most important spaceborne instrument for obtaining knowledge about global precipitation and latent heat [6][7][8][9][10]. In particular, its accumulated long-term record has been widely applied to climatological studies [11][12][13][14][15][16][17].…”
mentioning
confidence: 99%